(untitled) (BIS Humanities and Social Science, 2026)
Sustainability has become a major concern in the global tourism industry, including in priority destinations in Indonesia such as Magelang, where the hospitality sector plays an important role in balancing economic, social, and environmental dimensions. In this context, ethical communication and socially oriented organizational practices are key elements in supporting sustainable tourism development. This study examines how hospitality organizations in Magelang City implement sustainability principles through communication and social interaction that reflect the Fully Functioning Society Theory (FFST) concept. Using a descriptive qualitative approach, this study focuses on two major hotels, Puri Asri Hotel & Resort (five stars) and Atria Hotel (four stars) as case studies. Data were collected through in-depth interviews, field observations, and documentation. Analysis was conducted using the Full Functioning Society Theory (FFST) framework to understand how organizational communication patterns, values, and interactions contribute to the formation of a socially responsive and well-functioning hospitality environment. The findings show that all three hotels implement sustainability-oriented communication practices through cooperation with local farmers and MSMEs, regular evaluations with suppliers, and involvement in community-based tourism activities. These initiatives build mutual trust, strengthen stakeholder relationships, maintain operational stability, and reinforce the hotels’ position as supporters of sustainable tourism in Magelang. This study concludes that a fully functional hospitality organization is not only measured by its economic performance, but also by its ability to build ethical communication, reciprocal relationships, and community-oriented practices to improve social welfare and long-term tourism sustainability.